FAKTOR PENYEBAB RENDAHNYA SELF EFFICACY PADA SISWA SMP YANG MENGALAMI FATHERLESS - Griselda Grahita Komala (SHINE: JURNAL BIMBINGAN DAN KONSELING, 2024)
Identify the variables that contribute to students' low self-efficacy when they do not recognize the importance of dads in their personal development. In this sense, the absence of the father figure has a impact on how kids will be succes in academic settings. Children who witness fatherlessness do not find the father's role as an authority figure in the household to be clear-cut or even lost. Method of gathering data that were employed were observation and literature review. The study's findings demonstrate how crucial parental conflict is for kids. Low self-efficacy individuals require parental support, encouragement, and attention in the classroom.